2019
DOI: 10.1186/s12909-019-1776-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a modified doctor–patient communication training Programme designed for surgical residents in China: a prospective, large-volume study at a single Centre

Abstract: Background Effective doctor-patient communication (DPC) is important to improve the quality of care and treatment outcomes. This study aimed to evaluate the effectiveness of a modified DPC training programme designed for surgical residents in China. Methods A total of 210 surgical residents from 7 specialties were recruited to participate in a communication skills training programme. The extended SEGUE scale was administered to supervisors, and a visual analogue scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 28 publications
0
21
0
5
Order By: Relevance
“…Communication skills training curriculum has been introduced into China for more than 10 years, and have been increasingly described in some other medical disciplines, including surgery and oncology recently [4,12]. These studies have demonstrated that communication skills training program can improve the communication competency of residents.…”
Section: Discussionmentioning
confidence: 99%
“…Communication skills training curriculum has been introduced into China for more than 10 years, and have been increasingly described in some other medical disciplines, including surgery and oncology recently [4,12]. These studies have demonstrated that communication skills training program can improve the communication competency of residents.…”
Section: Discussionmentioning
confidence: 99%
“…Communication skills training curriculum has been introduced into China for more than ten years, and have been increasingly described in some other medical disciplines, including surgery and oncology recently 12,13 . These studies have demonstrated that communication skills training program can improve the communication competency of residents.…”
Section: Discussionmentioning
confidence: 99%
“…The SEGUE framework and General Self‐Efficacy Scale (GSES) were used as external criteria to assess the criterion validity of the NCAAPS. The SEGUE framework consists of two sections (doctor–patient communication content and communication skills) and five dimensions (preparation, information collection, information giving, understanding the patient and ending) (Makoul, 2001), and this scale has been used to evaluate communication skills in medical students (Sattler et al., 2017), nursing students (Son & Hee Kim, 2019) and doctors (Bai et al., 2019). The SEGUE framework has a Cronbach's α coefficient, CVI, test–retest reliability and KMO all exceeding 0.8 (Makoul, 2001; Xiong et al., 2019).…”
Section: The Studymentioning
confidence: 99%
“…For example, the Communication Skills Inventory developed by (Ersanli and Balci (1998) measures three dimensions of communication (psychology, emotion and behaviour) and consists of 45 questions answered using a 1–5 Likert scale. The Set Elicit Give Understand End (SEGUE) framework was developed by Makoul (2001) to evaluate the effectiveness of teaching and training in medical communication skills and has been used to assess communication ability in medical students (Sattler et al., 2017), nursing students (Son & Hee Kim, 2019) and qualified physicians (Bai et al., 2019). The Jefferson Empathy Scale (Hojat et al., 2002), which includes 20 items covering three dimensions (psychological cognition, emotional experience and behavioural assistance), has good internal consistency reliability and validity and has been translated into many different languages.…”
Section: Introductionmentioning
confidence: 99%